THE EFFECTIVENESS OF USING DIGITAL TECHNOLOGIES IN TEACHING ENGLISH IN GENERAL EDUCATION SCHOOLS OF UZBEKISTAN (SCIENCE TIME JOURNAL, 2026)
The article evaluates digital technologies in English teaching for Uzbekistan's general education schools through its literature analysis and theoretical assessment. The study analyzes current trends in digital pedagogy, explores the technological infrastructure available in Uzbek schools, and evaluates various digital tools and platforms used in English language instruction. The article identifies key challenges and opportunities in implementing digital solutions for English language teaching, considering the specific socio-educational context of Uzbekistan.